Effect of Mackerel Oil During Pregnancy on Synapsin Expression in Newborn Rattus Novergius Cerebrum - Siti Nur Kholifah; Widjiati Widjiati; Hermanto Tri Joewono; Ali Medina; Mikra Latisfian (Jurnal Kebidanan, 2023)
The increase in the number of cells indicates a good synapse function, so that it can be linked to human intelligence. The rapid rate of synaptogenesis, myelination occurs in the first 1000 days of life. The public has not realized the importance of nutrition during pregnancy which contributes to the intelligence of the baby that will be born later. One of them is mackerel oil which contains omega 3. This study aims to analyze the effect of mackerel oil during pregnancy on synapsin expression in the cerebrum. This type of research is true experimental with a posttest-only control group design. The research samples were 30 pregnant Rattus norvegicus mothers aged 2-3 months. The 3 groups were randomly divided namely the control group (K1), the mackerel fish oil treatment group (K2), and the treatment group who were given omega-3 supplements (K3). This research was conducted at the Experimental Animal Cages and Pathology Laboratory, Faculty of Veterinary Medicine, Airlangga University. ANOVA test results on synapsin expression in the cerebrum showed that there was a significant difference with a p-value of 0.000. Synapsin expression in the cerebrum of newborn Rattus norvegicus which was given mackerel oil in the mother of Rattus norvegicus during pregnancy showed higher results than other groups.